Community-based ecotourism in rural landscapes: Integrating global sustainability frameworks with local environmental governance - Muhammad Fadhli Fadhillah (Institute of Advance Science, Social, and Sustainable Future, 2026)
Background: This study investigates the implementation of community-based ecotourism as a strategy for advancing the United Nations Sustainable Development Goals (SDGs), focusing on its dual role in promoting environmental conservation and strengthening local economic resilience. A fundamental disconnect persists between universal sustainability principles and their practical application within complex local governance systems, creating a critical research gap. Methods: Employing a qualitative case study approach grounded in Ribot & Peluso's (2003) Theory of Access, this research analyzes the intricate power dynamics and access mechanisms within a community-based ecotourism initiative in Sanghyang Kenit, Indonesia. The study deconstructs interactions across a multi-stakeholder network involving PT X, Karang Taruna youth organization, Village Government, and the Citarum Harum Task Force. Findings: The analysis reveals that benefit streams and control over ecotourism commons are governed by dynamic